Investigating the applicability of low-cost sensors for ground-based air quality monitoring networks in developing countries: a Ghana case study. - Gameli Hodoli, Collins (Cranfield University, 2020)
While several studies have reported on the utility of low-cost sensors for air quality campaigns in advanced countries including the development of data correction and quality improvement mechanisms thereby using them to complement regulatory monitors, there is, in contrast, limited information on the use of low-cost sensors for air pollution applications in Ghana and wider parts of Sub-Saharan Africa. This PhD study presented a proof of concept approach on the feasibility of factory calibrated Alphasense OPC-N2 for two main purposes. Firstly, the suitability of low-cost sensors for high-density ground-based air pollution studies and the applicability of the high-resolution data for quantification of atmospheric emissions. Pearson’s correlation analysis was applied to establish the reproducibility of the selected sensors for high-density ground-based air quality monitoring specifically for PM species due to the spatial and temporal variability and suitability of PM for developing urban air quality standards. Trend analysis, calendar plots and sectorial plots in the components of wind were experimented using the high-resolution data to quantify particulate matter (PM) and its sources. Hourly averaged data from the selected sensors have demonstrated the reproducibility of low-cost OPC-N2 for use in the selected environments for PM with correlation coefficients (Pearson’s, R) between 0.97 and 0.98 for PM₁ , PM₂.₅ and PM₁₀. For quantification of the species monitored, PM₁ 0 values were 500 µg/mᶟ; PM₂.₅ were a little below 90 µg/mᶟ and PM₁ values were a little below 60 µg/mᶟ. These levels though preliminary, agree with PM pollution reported from these types of environments. It was also found that PM pollution was locally characterised with low wind speed (≤ 2 ms⁻¹) tied to background activities and the surrounding environment which includes traffic, wind-blown dust and roadside food cooking and vending activities. The statistical difference in mean values (t-values of 17.3, 11.4 and 4.2 for PM₁ , PM₂.₅ and PM₁₀ respectively) of the reported PM species have shown that the sensors are better suited for PM₁₀ monitoring. Findings from this study provide a benchmark for future (AQ) studies in Ghana, particularly in the selected exemplar urban areas. It demonstrates the feasibility of the current generation of relatively low-cost PM sensors for a high-density ground-based air quality monitoring in environments typical of large parts of West and Sub Saharan Africa.
Keywords: Air pollution; Ghana; sub-saharan Africa; low-cost sensing; air quality; atmospheric emissions